Evaluation of Lipid Peroxidation and Antioxidants’ Status in Metabolic Syndrome - Shrestha, S; Chandra, L; Aryal, M; Das, B K L; Pandey, S; Baral, N (Kathmandu University Medical Journal, 2012)
Background Metabolic syndrome is a constellation of physical conditions and metabolic abnormalities, commonly occurring together, that increases an individual’s risk for development of type 2 diabetes mellitus and cardiovascular diseases. Oxidative stress is associated with diabetes, hypertension and other cardiovascular diseases while the role of oxidative stress in pathogenesis of MS is not clearlydefined. Objectives The study aims to find out the prevalence of metabolic syndrome in faculty and staff members at BP Koirala Institute of Health Sciences, Dharan, Nepal and to evaluate oxidative stress levels insubjects with metabolic syndrome. Methods 118 healthy participants working at B. P. Koirala Institute of Health Sciences, Dharan, Nepal were selected at random for this cross-sectional study and blood samples were collected for the estimation of the following biochemical analytes; fasting glucose; triglycerides; total cholesterol; high density lipoprotein cholesterol; Albumin; uric acid; Bilirubin; Malondialdehyde; Catalase; Glutathione peroxidase; Superoxide Dismutase; Glutathione; vitamin C; and lastly vitamin E. Results In this cross-sectional study, 39% subjects were diagnosed with metabolic syndrome , particularly in sedentary subjects. There was no difference in oxidative stress except significant rises in serum uric acid levels and catalase activity in subjects diagnosed with metabolic syndrome . Conclusion The prevalence of metabolic syndrome is higher without oxidative stress in this study, which suggests that oxidative stress does not contribute to the pathogenesis of MS in otherwise healthy subjects. http://dx.doi.org/10.3126/kumj.v8i4.6236 Kathmandu Univ Med J 2010;8(4):382-6